Islam beyond borders the umma in world politics - Piscatori, James P. 1949-; Saikal, Amin 1950- (Cambridge University Press, 2019)
Assuming a central place in Muslim life, the Qur'an speaks of one community of the faith, the umma. This unity of the faithful is recognised as the default aspiration of the believer, and in the modern era, intellectuals and political leaders have often vied both to define, and to lead it. Based on case studies of actors such as Saudi Arabia, Iran, and ISIS, James Piscatori and Amin Saikal consider how some appeals to pan-Islam prove useful, yet other attempts at cross-border institutionalisation including the Sunni Caliphate or the modern Shi'i-inspired Islamic Revolution, founder on political self-interest and sectarian affiliations. Accompanied by a range of scriptural references to examine different interpretations of the umma, Piscatori and Saikal explore why, despite it meaning such widely different things, and its failure to be realised as a concrete project, neither the umma's popular symbolic appeal nor its influence on a politics of identity has diminished
Title from publisher's bibliographic system (viewed on 09 Sep 2019)
Introduction -- Sunni constructions of the umma -- Shi'a Islam and the umma -- Saudi "guardianship" of the umma -- ISIS's conception of the umma -- Conclusion
Keywords: IS (Organization); Ummah (Islam); Islam and politics; Internationale Politik; Umma -- Religion; Weltpolitik; Islamische Staaten